Virtual consultation in kidney care: a mixed-methods study on a model for safe and effective integration into routine clinical care - Aminu K Bello; Stephanie Thompson; Deenaz Zaidi; Scott Klarenbach; Feng Ye; Terry J Smith; Mark Courtney (BMJ Open)
Rationale and Objective Globally, the COVID-19 pandemic necessitated a rapid introduction of virtual care delivery via telephone or videoconference. The rapid advancements in e-health technology facilitated options for virtual care, including asynchronous data transfer in virtual clinic models and patient-facing smartphone applications for communications and self-care. However, the clinical benefits of virtual consultation have not been consistently demonstrated in all facets of kidney care, and the adoption of this innovation alters workflows and health professionals’ perceptions of care delivery. This study evaluated the integration of virtual outpatient consultation safely and effectively into the kidney care programme in Alberta.Study design We leveraged a mixed-methods approach to collate data about clinicians’ experiences and opinions, forming the basis for the qualitative part of the study.Data extraction Data were collected through surveys, interviews and focus groups of nephrologists and home dialysis nurses.Analytical approach Focus group/interview transcripts for nephrologists and nurses were used to generate initial codebooks, which were iteratively refined throughout the analysis. Codes were categorised and analysed thematically, and data collected from nephrologists and nurses were analysed separately.Results The findings demonstrated that clinicians support the use of routine virtual care. Clinicians’ opinions on implementation requirements emphasised logistics for routine virtual care integration, quality of care delivered, impacts on the therapeutic relationship and regulatory policy clarification.Limitation The generalisability of the findings is limited in scope, as the study was conducted in a single nephrology programme in Canada, and may not apply to other provinces or settings.Conclusions These findings inform recommendations for safe and effective virtual care delivery and can be leveraged to inform virtual care designs in kidney care programmes. Further study is required to clarify the impacts of virtual care on specific population demographics based on geography (rural vs urban) and age (elderly population) in the post-COVID-19 era, and determine how to effectively integrate patient perspectives into this model of care.